Iturin A Extracted From Bacillus subtilis WL-2 Affects Phytophthora infestans via Cell Structure Disruption, Oxidative Stress, and Energy Supply Dysfunction - Wang, Youyou; Zhang, Congying; Liang, Jiao; Wu, Lufang; Gao, Wenbin; Jiang, Jizhi (Frontiers in Microbiology, 2020)
Potato late blight, caused by Phytophthora infestans (Mont.) de Bary, represents a great food security threat worldwide and is difficult to control. Recently, Bacillus spp. have been considered biocontrol agents to control many plant diseases. Here, Bacillus subtilis WL-2 was selected as a potent strain against P. infestans mycelium growth, and its functional metabolite was identified as Iturin A via electrospray ionization mass spectrometry (ESI-MS). Analyses using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed that Iturin A caused cell membrane disruption and irregular internal cell structure. In addition, Iturin A triggered oxidative stress reactions similarly to reactive oxygen species (ROS) in P. infestans cells and caused mitochondrial damage, including mitochondrial membrane potential (MMP), mitochondrial respiratory chain complex activity (MRCCA), and ATP production decline. These results highlight that the cell membrane damage, oxidative stress, and mitochondrial dysfunction induced by Iturin A play an important role in inhibiting P. infestans. Additionally, B. subtilis WL-2 and Iturin A have great potential for inhibiting P. infestans mycelium growth and controlling potato late blight in the future.